PENGARUH KUALITAS LAYANAN DAN CITRA RUMAH SAKIT TERHADAP KEPUASAN DAN KEPERCAYAAN PASIEN DI SENTRA MEDIKA HOSPITAL CIBINONG - Armand Helmy; Bernard T. Widjaja; Fushen, Fushen (Bajang Institute, 2025)
A hospital is a personal health care facility that provides basic and/or specialist medical services (Ministry of Health, 2024). Sentra Medika Hospital Cibinong is one of the private facilities that provides first-level health services that function as Individual Health Efforts (UKP) and Public Health Efforts (UKM) with the aim of improving health standards in the designated work area. Sentra Medika Hospital Cibinong is the number of outpatients that tends to fluctuate. While on the one hand, outpatients are one source of income for a hospital because the number of patients is greater and for patients suffering from certain diseases tend to be consistent over a certain period of time. For this reason, it is important for Sentra Medika Hospital Cibinong to pay attention to the satisfaction of outpatients because if patients feel dissatisfied, it will be easy to change their minds and switch to using health services from other hospitals, but when patients feel satisfied, it is more difficult to change their choices. This study uses a quantitative method with SEMPLS calculations. The results of this study did not have a positive effect between service quality and patient trust at Sentra Medika Hospital Cibinong. Therefore, hospitals should routinely evaluate the quality of services in order to find out how the services provided are in accordance with patient expectations